2016
DOI: 10.3390/en9040234
|View full text |Cite
|
Sign up to set email alerts
|

S-Rich CdS1−yTey Thin Films Produced by the Spray Pyrolysis Technique

Abstract: Understanding the properties of CdSTe ternary alloys is important because they always form at the interface between the CdS window layer and CdTe absorber layer in CdS/CdTe solar cells due to the intermixing. This interdiffusion is necessary because it improves the device performance. Experimental work has been devoted to studying Te rich p-type CdS x Te 1´x alloys, but there is a lack of studies on S-rich n-type CdS 1´y Te y solid solutions. In this work, a review of the structure, morphology, and optical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The CdS-CdTe solid solutions can grow in the cubic (zinc blende) phase, the hexagonal (wurtzite) phase or the mixed (cubic and hexagonal) phase [6,7]. CdTe1−xSx has the crystallographic form of the zinc blende (ZB) with space group (F-43m) structure, and CdS1−yTey the wurtzite (WZ) structure with space group (P63mc).…”
Section: Structural Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The CdS-CdTe solid solutions can grow in the cubic (zinc blende) phase, the hexagonal (wurtzite) phase or the mixed (cubic and hexagonal) phase [6,7]. CdTe1−xSx has the crystallographic form of the zinc blende (ZB) with space group (F-43m) structure, and CdS1−yTey the wurtzite (WZ) structure with space group (P63mc).…”
Section: Structural Propertiesmentioning
confidence: 99%
“…The mixed phase of the CdS-CdTe system shows a large miscibility gap that depends on temperature in which both phases (cubic and hexagonal) are present. Compaan and Bohn [6,11] found that the miscibility gap of CdTe1−xSx spans the range between x = 0.16 to x = 0.86 at a temperature of T = 650°C, Duenow et al [9] showed that it spans the range between x = 0.058 and x = 0.97 at a temperature of 415°C. Single-phase films that exist within this gap are not in thermodynamic equilibrium, and hence, one should expect a large driving force for decomposition or phase separation in the material [11].…”
Section: Structural Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cadmium sulfide is one of the most studied semiconductors for the photocatalytic hydrogen ion reduction, CO 2 reduction, and photovoltaics. ,, This is due to its small band gap energy (ca. 2.3–2.6 eV) and suitable band energy alignment.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical calculations suggest a maximum efficiency around 30% in CdTe-based solar cells (Santana-Aranda and Melendez-Lira, 2000;Morales-Acevedo, 2006). An interdiffusion process occurring at the CdS-CdTe interface during cell production has been pointed out as one of the efficiency limiting factors (Hadrich et al, 2009;Ikhmayies, 2016). Thus, it is important to have a full understanding of the properties of ternary compound CdS x Te 1-x .…”
Section: Introductionmentioning
confidence: 99%